Răspuns :
[tex] log_{3} ( x^{2} -2x)= log_{3} (2x-3)[/tex]
deoarece logaritmii au aceiasi baza delogaritmezi
x²-2x=2x-3
x²-4x+3=0
Δ=16-4*3=16-12=4
x1=(4-√4)/2=2/2=1
x2=(4+√4)/2=6/2=3
Veifici solutiile
[tex] log_{3} (1-2)= log_{3} (-1) imposibil[/tex]
[tex] log_{3} ( 3^{2} -2*3)= log_{3} (2*3-3)[/tex]
[tex] log_{3} 3= log_{3} 3[/tex]
1=1 adevarat x=3 solutie.
deoarece logaritmii au aceiasi baza delogaritmezi
x²-2x=2x-3
x²-4x+3=0
Δ=16-4*3=16-12=4
x1=(4-√4)/2=2/2=1
x2=(4+√4)/2=6/2=3
Veifici solutiile
[tex] log_{3} (1-2)= log_{3} (-1) imposibil[/tex]
[tex] log_{3} ( 3^{2} -2*3)= log_{3} (2*3-3)[/tex]
[tex] log_{3} 3= log_{3} 3[/tex]
1=1 adevarat x=3 solutie.